New horizons from novel therapies in malignant pleural mesothelioma - (:unkn) unknown (VIA MEDICA, 2022)
Malignant pleural mesothelioma (MPM) is a relatively rare, but highly lethal cancer of the pleural mesothelial cells. Its pathogenesis is integrally linked to asbestos exposure. In spite of recent developments providing a more detailed understanding of the pathogenesis, the outcomes continue to be poor. To date, trimodality therapy involving surgery coupled with chemotherapy and/or radiotherapy remains the standard of therapy. The development of resistance of the tumor cells to radiation and several chemotherapeutic agents poses even greater challenges in the management of this cancer. Ionizing radiation damages cancer cell DNA and aids in therapeutic response, but it also activates cell survival signaling pathways that helps the tumor cells to overcome radiation-induced cytotoxicity. A careful evaluation of the biology involved in mesothelioma with an emphasis on the workings of pro-survival signaling pathways might offer some guidance for treatment options. This review focuses on the existing treatment options for MPM, novel treatment approaches based on recent studies combining the use of inhibitors which target different pro-survival pathways, and radiotherapy to optimize treatment.
Keywords: mesothelioma; chemotherapy; radiotherapy; targeted therapy; immunotherapy; GROWTH-FACTOR RECEPTOR; ELEMENT-BINDING PROTEIN; OPEN-LABEL; PHASE-II; NEUROENDOCRINE DIFFERENTIATION; SIGNALING PATHWAY; ZOLEDRONIC ACID; DOUBLE-BLIND; SINGLE-ARM; CANCER